Status and frontiers of Fabre disease - Wei Chu; Min Chen; Xiaoqin Lv; Sheng Lu; Changyan Wang; Limin Yin; Linyan Qian; Jiana Shi (Orphanet Journal of Rare Diseases)
Abstract Fabry disease is characterized by an X sex chromosome gene mutation caused by α-galactosidase A deficiency, resulting in the accumulation of globotriaosylceramide and globotriaosylsphingosine in various organs, which induces end-organ lesions. In Fabry disease, enzymes with lost or decreased activity in the body are replaced by exogenous supplementation of normal-function α-galactosidase A. Currently, agalsidase α and agalsidase β are widely used for ERT therapy. However, this therapy has limitations such as high cost, short half-life, and production of neutralizing drug antibodies. The use of Migalastat as chaperone therapy has been approved in many countries, and it plays a therapeutic role by enhancing enzyme activity. However, companion therapy drugs are only suitable for patients with decreased enzyme activity, so the scope of their application is limited. In addition, there are several therapeutic drugs in development, including a new generation of ERT therapies, drugs resistant to neutralizing anti-drug antibody drugs, and substrate reduction therapy drugs. Due to the limitations of existing therapeutic drugs, researchers have begun to explore new therapeutic drugs for Fabry disease, so new pathogenic mechanisms and adjuvant therapeutic drugs have been continuously discovered, and the development of related drugs will contribute to disease control and treatment. This article summarizes the existing and potential drugs for treating Fabry disease to facilitate the selection of suitable and effective drugs for treatment.